대량의 쌀 시료 분석을 위한 DNA 추출법 - 최영덕; Young Deok Choi; 이해광; Hae Kwang Lee; 이윤숙; Yun Suk Lee; 윤정희; Jeong Hee Yun; 김수정; Su Jeong Kim; 박성환; Seong Whan Park (Korean journal of crop science, 2006)
The study of molecular markers to improve crops largely depends on the availability of rapid and of efficient DNA extraction methods. Here we developed a cheap and convenient method to isolate genomic DNA from rice grains suitable for large-scale microsatellite analysis. We confirmed that the isolated rice DNA is suitable for PCR analysis with STS marker and SNP marker, as well as microsatellite marker. Further, we established high-throughput DNA extraction system in a 96-well plate format which make it possible high-throughput analysis of microsatellite markers with rice grains. This implies that the new method could be a useful tool for other types of marker analysis in large scale.